التحليل المكاني للمواكب الحسينية في مدينة الكوت - عطاالله عبد الجليل ضاري; كاظم مروة جواد (Journal of College of Education, 2018)
The study aims to know the reality of the spatial distribution of religious processions in the city of Kut and know its efficiency for the city, find out by (GIS), and use statistical patterns As the nearest neighbour and standard distance, as the four city sectors processions are divided practically this indicates the homogeneous distribution of smoothing processions in the city and the neighboring link between processions in sectors of the city far apart and this shows that the distribution of deployment are regularly in these sectors. Standard distance and surface area varies between the four sectors of the city.